Policies and Research in Identity Management: Third IFIP WG 11.6 Working Conference, IDMAN 2013, London, UK, April 8-9, 2013, Proceedings - Fischer-Hubner, Simone; Leeuw, Elisabeth de; Mitchell, Chris J (IFIP Advances in Information and Communication Technology, 2013)
This book constitutes the refereed proceedings of the Third IFIP WG 11.6 Working Conference on Policies and Research in Identity Management, IDMAN 2013, held in London, UK, in April 2013. The 6 refereed full and 4 short papers presented together with 3 short position papers and a keynote paper were selected from 26 submissions. The papers have been organized into topical sections on privacy and identity management, anonymous credentials, authentication and access control, risk management of identity management, identity management with smart cards, and federated identity management.